2013
DOI: 10.2298/avb1306655k
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Salmonella Typhimurium in pork minced meat and pork skin at different storage temperatures

Abstract: Salmonella is a common contaminant of pork and can present a health hazard to consumers. Therefore, for an effective control, the entire supply chain must be involved. The aim of this paper is to examine the survival of Salmonella Typhimurium in pork minced meat and skin at different temperatures and time. In minced meat, stored at +4 ± 0.5 o C during 72 h, the number of Salmonella Typhimurium of all three examined strains A, B, and C decreased (p<0.01). In minced meat, stored at +10 ± 1 o C after 72 h, the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Salmonella species are highly resistant microorganisms, able to survive longer periods in foods where its multiplication for some reason is not possible [25]. The optimum pH values for the growth of most Salmonella species ranged from 6.5-7.5, but they can grow in the range of 4.5-9.0.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella species are highly resistant microorganisms, able to survive longer periods in foods where its multiplication for some reason is not possible [25]. The optimum pH values for the growth of most Salmonella species ranged from 6.5-7.5, but they can grow in the range of 4.5-9.0.…”
Section: Discussionmentioning
confidence: 99%
“…Scuderi with colleagues (2000) reported that every year from various sources collected in Italy about 10,000 of salmonella isolates are registered, with over 70% of human infections caused by serovars of S. Typhimuruim, S. Enteritidis and S. Infantis [29]. Prevalence of salmonella in fresh meat is directly related to the fi ndings in animals and, of course, depends on further technological processing in slaughterhouses [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to low temperature and decreased water activity due to the air flow in the cooling room. Unlike minced meat, which contains fat and can protect Salmonella from low temperatures, skin surface dries quickly, which is not favorable for Salmonella [19]. Salmonella was found in five samples of the ileal content in our investigation.…”
Section: Discussionmentioning
confidence: 57%